2017
DOI: 10.21595/jve.2016.17895
|View full text |Cite
|
Sign up to set email alerts
|

Centrifuge shaking table tests on effect of vertical drain systems for liquefied soil

Abstract: It was observed that liquefaction induced by earthquake causes series damages to buildings and threatens the people and their properties. From the past studies, a number of countermeasures were proposed to reduce the build-up of excess pore water pressure and to enhance the stiffness of the soil during earthquake. The vertical drain systems are well known methods and used as remediation against earthquake-induced soil liquefaction for many years. The purpose of the study is to investigate the effect of differe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Most tailings dam failures are induced by seismic events that trigger displacements and/or deformations due to increased interstitial pressures generating the potential development of liquefaction. Moreover, it is the main factor influencing instability, it is concluded that failure mechanisms directly affect the instability of the containment structure causing an increased risk of collapse [18]. The main cause of dam failures is the liquefaction phenomenon, so international standards have classified the type of tailings dams and the consequences of environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…Most tailings dam failures are induced by seismic events that trigger displacements and/or deformations due to increased interstitial pressures generating the potential development of liquefaction. Moreover, it is the main factor influencing instability, it is concluded that failure mechanisms directly affect the instability of the containment structure causing an increased risk of collapse [18]. The main cause of dam failures is the liquefaction phenomenon, so international standards have classified the type of tailings dams and the consequences of environmental impact.…”
Section: Introductionmentioning
confidence: 99%
“…The hypergravity centrifugal shaking table [1,2] is mainly composed of two parts: a centrifuge that generates an additional heavy force field and an airborne shaking table that is used to reproduce highfrequency seismic waveforms. By using a large centrifuge to attach the heavy force field of the airborne shaking table, the stress equivalence between the scale experiment under hypergravity and the original physical model experiment under normal gravity is realized.…”
mentioning
confidence: 99%